Putting the consumer in the driver's seat: A visual journey through the Australian health‐care system as experienced by people living with dementia and their carers. (8th September 2019) - Fitzgerald, Janna Anneke; Curry, Joanne; Olde Meierink, Angelique; Cully, Ashley
Abstract: Objective: To better understand the individual journeys of people living with dementia and their carers through the Australian health‐care system. Methods: Stories were collected from 25 participants, through five face‐to‐face workshops, across Australia. This produced 18 visual storyboards and a range of opportunities for improvement, which were then synthesised into an aggregated "ideal‐journey" model. Results: Several issues were identified: long lead times to diagnosis; diverse experiences of treatment and support; and little coordination of care or thought for its impact on the consumer. Information about services, their purpose and eligibility criteria was difficult to obtain, and potential care pathways were largely unexplained. Much of the carer support received was reactive rather than proactive. Conclusions: A better understanding of the current health‐care pathway of dementia is essential for the design and delivery of future health‐care services. It is vital to include the consumer voice in future research and allocation of health‐care resources.